Enhanced learning strategies of undergraduate medical students with a structured case presentation format - Sarabmeet Singh Lehl; Monica Gupta; Sanjay D'Cruz (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Improvement of the learning in undergraduate bedside teaching needs to be promoted through innovative interventions. Changes in the structured format (SF) for bedside case discussion may help students improve their learning experience and gain insights into collaborative self-directed learning. The aim of the present study was to encourage collaborative and self-directed learning strategies by MBBS undergraduate students through a new case presentation format structured for this purpose. MATERIALS AND METHODS: This was an interventional study carried out in the year 2010-2011. A new SF for bedside cases presentation was developed. A comparison with the traditional format was done by holding one session in each format. Uniformity of topic and teaching style was ensured by having the sessions on pulmonary medicine cases with the same teacher. The student perspective of the educational process was analyzed using evaluation pro forma, Likert scale, and narratives. RESULTS: Ninety final year and prefinal year MBBS students participated in this study. There was significantly higher participation in history taking (50.7%) and clinical examination (60%) in the SF. A higher statistically significant number of clinical possibilities were considered in the SF (85.3% vs. 66.6%). Similarly, significantly higher number of students indulged in self-directed learning and referred to learning resources in the SF. The SF provided students an active role (96.9%), encouraged access to resources (93.9%), and control of learning (75.7%). The additional interactive session was productive (90.9%), discussions were streamlined (66.6%), and the role of a teacher was considered important (75.7%). CONCLUSION: The SF generated higher participation in the aspects of history taking, clinical examination, and consideration of differential diagnoses. It led to a perceived improvement in self-directed and collaborative learning among students.